Phase and absorption retrieval using incoherent X-ray sources - Munro, Peter R.T. (National Academy of Sciences, 2012)
X-ray phase contrast imaging has overcome the limitations of X-ray absorption imaging in many fields. Particular effort has been directed towards developing phase retrieval methods: These reveal quantitative information about a sample, which is a requirement for performing X-ray phase tomography, allows material identification and better distinction between tissue types, etc. Phase retrieval seems impossible with conventional X-ray sources due to their low spatial coherence. In the only previous example where conventional sources have been used, collimators were employed to produce spatially coherent secondary sources. We present a truly incoherent phase retrieval method, which removes the spatial coherence constraints and employs a conventional source without aperturing, collimation, or filtering. This is possible because our technique, based on the pixel edge illumination principle, is neither interferometric nor crystal based. Beams created by an X-ray mask to image the sample are smeared due to the incoherence of the source, yet we show that their displacements can still be measured accurately, obtaining strong phase contrast. Quantitative information is extracted from only two images rather than a sequence as required by several coherent methods. Our technique makes quantitative phase imaging and phase tomography possible in applications where exposure time and radiation dose are critical. The technique employs masks which are currently commercially available with linear dimensions in the tens of centimeters thus allowing for a large field of view. The technique works at high photon energy and thus promises to deliver much safer quantitative phase imaging and phase tomography in the future.